An Investigation of the Environmental Quality through Anthropogenic Metal Analysis in Targeted Niger Delta Aquatic Systems, Nigeria - Nurudeen Onomhoale Ahmed; Nik Norsyahariati Nik Daud; Ipoola Ajani Okunlola (Geography, Earth Science and Environment: Research Highlights Vol. 2, 2024)
Background: Water, an essential resource for life and ecosystems, faces increasing threats due to the escalating pace of industrialization, particularly in oil-rich regions like the Niger Delta in Nigeria. This area is a hotspot for petroleum production, where extensive gas flaring and illicit artisanal activities introduce substantial pollutants into the environment, directly impacting the quality of surface and rainwater. Aims: This study aims to investigate the impact of anthropogenic activities, particularly oil industry operations, on environmental quality in the Oyigbo Local Government Area (L.G.A.), Rivers State, Nigeria, focusing on evaluating heavy metals in water sources affected by gas flaring and petroleum production. Study Design: This is an environmental quality assessment study, utilizing geochemical and geospatial analysis of water to determine the distribution and impact of heavy metals. Place and Duration of Study: The study was conducted in the Oyigbo L.G.A., Rivers State, Niger Delta, Nigeria, within a duration of 275 days. Methodology: A total of 41 water samples were collected, including 34 rainwater and 7 river water samples. The concentrations of four key heavy metals, lead (Pb), copper (Cu), cadmium (Cd), and zinc (Zn), were analyzed. Two indices, the Heavy Metals Pollution Index (HPI) and the Potential Ecological Risk Index (PERI), were calculated to assess the environmental impact of these metals. Geospatial distribution analysis was performed to identify contamination hotspots. The geospatial analysis involved mapping the spatial distribution of heavy metal concentrations (Pb, Cu, Cd, and Zn) at various locations using ArcGIS 10.4 and Microsoft Excel. Results: Pb levels in rainwater ranged from 0.11 to 2.42 mg/L, with locations like Atata and Okoloma Market, showing concentrations far exceeding the World Health Organization (WHO) limit of 0.01 mg/L. River samples also had high Pb levels, peaking at 1.21 mg/L. Cu, Cd, and Zn concentrations were generally within acceptable limits, with Cu ranging from 0.08 to 0.43 mg/L, Cd consistently below 0.003 mg/L, and Zn between 0.018 and 2.011 mg/L. Conclusion: The HPI identified Pb as the predominant contaminant, and the PERI classified the overall pollution risk as slight, with Pb posing the highest ecological threat. Geospatial analysis revealed Pb contamination was most severe in the northern-central and western parts, while Zn showed localized higher levels, suggesting specific pollution sources. The study highlights the urgency to address Pb contamination, posing significant risks to the area’s environmental and public health. Educating local communities on contamination risks, promoting water purification methods, and supporting ongoing research to monitor vulnerable areas will be essential for safeguarding public health and the environment.